2016
DOI: 10.1002/ejp.897
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of sigma 1 receptors alleviates sensory signs of diabetic neuropathy in rats

Abstract: BackgroundE‐52862 (S1RA, 4‐[2‐[[5‐methyl‐1‐(2‐naphthalenyl)‐1H‐pyrazol‐3‐yl]oxy]ethyl]‐morpholine), a novel selective sigma 1 receptor (σ1R) antagonist, has demonstrated efficacy in nociceptive and neuropathic pain models. Our aim was to test if σ1R blockade with E‐52862 may modify the signs of neuropathy in Zucker diabetic fatty (ZDF) rats, a type 2 diabetes model.MethodsMechanical and thermal response thresholds were tested on 7‐, 13‐, 14‐ and 15‐week‐old ZDF rats treated with saline or with E‐52862 acutely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
6
16
0
Order By: Relevance
“…There are few studies showing the vascular effects of the σ1R modulation (Hosszu et al., ; Tagashira et al., ), although some recent studies showed σ1R expression in vascular tissue (Amer et al., ; Bhuiyan, Tagashira, Shioda, & Fukunaga, ). The repeated administration of MR‐309 was able to correct both the increase in coronary perfusion pressure and endothelial dysfunction in the aorta, which agree with our previous recordings in diabetic rats, demonstrating that MR‐309 treatment can improve vascular parameters (Paniagua et al., ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There are few studies showing the vascular effects of the σ1R modulation (Hosszu et al., ; Tagashira et al., ), although some recent studies showed σ1R expression in vascular tissue (Amer et al., ; Bhuiyan, Tagashira, Shioda, & Fukunaga, ). The repeated administration of MR‐309 was able to correct both the increase in coronary perfusion pressure and endothelial dysfunction in the aorta, which agree with our previous recordings in diabetic rats, demonstrating that MR‐309 treatment can improve vascular parameters (Paniagua et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…It shows efficacy in nociceptive as well as neuropathic pain models. MR-309 demonstrated the antinociceptive effect of the σ1R blockade mainly develop for peripheral sensitization pain models, such as in capsaicin sensitization (Entrena et al, 2009), partial sciatic nerve ligation (Romero et al, 2012) and diabetic neuropathy (Paniagua et al, 2017).…”
mentioning
confidence: 99%
“…E-52862 has demonstrated efficacy in translationally driven neuropathic pain models, that is, chemotherapy-induced neuropathy [37] and diabetes-induced neuropathy [108]. E-52862 reduced dose-dependently both the development and the expression of cold and mechanical allodynia in paclitaxel-treated mice, in accordance with the results obtained in s 1 R KO mice, which did not develop paclitaxel-induced neuropathy [37].…”
Section: E-52862supporting
confidence: 64%
“…Similarly, single or repeated-dose administration of E-52862 reduced both mechanical allodynia and thermal hyperalgesia developed in Zucker Diabetic Fatty rats. At the electrophysiology level, diabetic rats treated with E-52862 showed a lower response to ramp or supra-threshold step mechanical stimulation compared to rats receiving vehicle in the skin-saphenous nerve preparation [108]. In an operant self-administration model, mice with partial sciatic nerve ligation, but not sham-operated animals, self-administered E-52862 to relieve pain.…”
Section: E-52862mentioning
confidence: 99%
“…administration of 101 demonstrated its dose‐dependent antinociceptive effect, without inducing motor impairment at these doses. Further studies emphasize the analgesic activity of 101 in neuropathic pain of different etiology, in rats …”
Section: Pharmacological Activity Of Morpholine Derivatives On Varioumentioning
confidence: 98%